The effect of non-opioid multimodal analgesics and dexamethasone monotherapy on acute incisional pain behaviors in rats - Banik, Ratan K.; Johns, Malcolm E.; Sia, Twan; Simone, Donald A. (Frontiers in Pain Research, 2025)
The use of non-opioid multimodal analgesics (NMA) may enhance pain relief and decrease opioid dependence in managing acute incisional pain, although this remains debated. A clinical trial found NMA ineffective compared to placebo, prompting us to investigate its impact on pain-like behaviors in animal models. In our study, 12 rats underwent plantar incision surgery and were divided into two groups: NMA and vehicle. NMA comprised acetaminophen, celecoxib, gabapentin, and dextromethorphan, with dosages based on human equivalents. We measured paw withdrawal latency (PWL), paw withdrawal threshold (PWT), and spontaneous foot lifting (SFL) behaviors. Before injection, there were no significant differences between the groups in PWL, PWT, or SFL. After treatment, PWL increased in NMA-injected rats (9.8 ± 2.2 s) compared to vehicle (5.9 ± 2.7 s; p = 0.02). SFL frequency decreased in NMA-injected rats (8.0 ± 5.0 count/20-min) vs. vehicle (30.7 ± 18.0 count/20-min; p = 0.013). However, PWT and SFL duration showed no significant changes. This research represents the first exploration of NMA's effects on incisional pain, suggesting it may effectively manage acute postsurgical pain with inflammatory and neuropathic components. Further clinical validation is needed, but our results indicate NMA could be a viable opioid alternative.